PDM4, a Pentatricopeptide Repeat Protein, Affects Chloroplast Gene Expression and Chloroplast Development in Arabidopsis thaliana - Wang, Xinwei; Zhao, Lirong; Man, Yi; Li, Xiaojuan; Wang, Li; Xiao, Jianwei (Frontiers in Plant Science, 2020)
Extensive studies have been carried out on chloroplast development; however, the regulatory mechanism still remains obscure. To investigate the molecular mechanism of chloroplast biogenesis and development, we characterized an Arabidopsis mutant pdm4 which showed seedling-lethal and albino phenotype under heterotrophic growth conditions. Electron microscopy demonstrated that the number of thylakoids was reduced and the structure of those thylakoids was disrupted in pdm4 mutant, which eventually led to the breakdown of chloroplasts. The levels of several chloroplast- and nuclear-encoded proteins are strongly reduced in pdm4 mutant. Besides, analysis of the transcript profiles of chloroplast genes revealed that plastid-encoded polymerase-dependent transcript levels were markedly reduced, while nuclear-encoded polymerase-dependent transcript levels were increased. In addition, we found that PDM4 functions in the splicing of group II introns and possibly also contributes to the assembly of the 50S ribosomal particle. Together, our results demonstrate that PDM4 plays an important role in chloroplast genes expression and chloroplast development in Arabidopsis.